2011
DOI: 10.1093/neuonc/nor131
|View full text |Cite
|
Sign up to set email alerts
|

RAD51 can inhibit PDGF-B–induced gliomagenesis and genomic instability

Abstract: Faithful replication and DNA repair are vital for maintenance of genome integrity. RAD51 is a central protein in homologous recombination repair and during replication, when it protects and restarts stalled replication forks. Aberrant RAD51 expression occurs in glioma, and high expression has been shown to correlate with prolonged survival. Furthermore, genes involved in DNA damage response (DDR) are mutated or deleted in human glioblastomas, corroborating the importance of proper DNA repair to suppress glioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…Several studies have demonstrated that activation of DDR-DNA repair system works as an oncogene-induced barrier against tumor establishment (Bartek et al, 2007;Squatrito and Holland, 2011), and mutations or alterations that lead to loss of function or downregulation could represent a trigger for gliomagenesis (Cha and Yim, 2013). In a study using a mouse model for glioma development, it was demonstrated that the induced expression of RAD51, a central protein for repair by homologous recombination (HR), decreases both the incidence of oncogene-induced glioma and the genomic instability, impairing carcinogenesis (Westermark et al, 2011). Using a similar model, Squatrito and colleagues showed that components of the DDR pathway are frequently altered in gliomas and loss of ATM or its downstream targets accelerates tumor formation (Squatrito et al, 2010).…”
Section: Dna Repair Functions In Tumorigenesis and Progressionmentioning
confidence: 99%
“…Several studies have demonstrated that activation of DDR-DNA repair system works as an oncogene-induced barrier against tumor establishment (Bartek et al, 2007;Squatrito and Holland, 2011), and mutations or alterations that lead to loss of function or downregulation could represent a trigger for gliomagenesis (Cha and Yim, 2013). In a study using a mouse model for glioma development, it was demonstrated that the induced expression of RAD51, a central protein for repair by homologous recombination (HR), decreases both the incidence of oncogene-induced glioma and the genomic instability, impairing carcinogenesis (Westermark et al, 2011). Using a similar model, Squatrito and colleagues showed that components of the DDR pathway are frequently altered in gliomas and loss of ATM or its downstream targets accelerates tumor formation (Squatrito et al, 2010).…”
Section: Dna Repair Functions In Tumorigenesis and Progressionmentioning
confidence: 99%
“…These hyperplasias had activated DNA damage response in terms of 53BP1 foci, phosphorylated histone H2AX and Chk2, increased p53 levels, and apoptosis likely as a result of DNA damage response ( 36 ). PDGF-B over-expression has also been shown to induce DNA damage response, genomic instability and ploidy in glial cells, and hyperplastic lesions of the brain and subsequent gliomas ( 37 ). Over-expression of cyclin E, common in cancer and rapidly cycling cells, results in increases in Ser 15-phosphorylated p53, γ-H2AX, and Ser 966-phosphorylated cohesin SMC1, which are all targets of the DNA damage response kinases ATM and ATR ( 34 ).…”
Section: Prolonged or Abnormal Growth Factor Signalingmentioning
confidence: 99%
“…Accumulated evidence has established critical roles for the tumor suppressor p53-binding protein 1 (53BP1) in non-homologous end-joining (NHEJ) double-stand break (DSB) DNA repair [3032], and Rad51 in homologous recombination (HR) DSB DNA repair [33]. In addition, 53BP1 and Rad51 are important for glioma tumorigenesis [6, 34]. Based on our results above, we hypothesized that G0S2 enhances radiation resistance of gliomas through regulation of Rad51 or 53BP1.…”
Section: Resultsmentioning
confidence: 99%